Implementation of Clinical Supervision in Improving Pedagogical Competence of Science Teachers in Experimental Material - Susi Wulandari; Nesi Anti Andini; Ma'rifatun Ni'mah (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the role of clinical supervision in improving science teachers’ pedagogical competence in experiment-based learning through a systematic literature review approach. Data were collected from national and international journal articles published between 2013 and 2024 indexed in Google Scholar, ERIC, Scopus, and DOAJ. A total of 35 articles were selected using PRISMA procedures and analyzed thematically. The findings indicate that clinical supervision contributes significantly to improving lesson planning, classroom management, instructional strategies, and authentic assessment in experimental science learning. Structured feedback, reflective dialogue, and continuous mentoring were identified as the main factors supporting teachers’ professional development. However, several challenges such as limited facilities, teacher workload, and supervisor competence still influence the effectiveness of implementation. This study highlights the importance of structured clinical supervision as a sustainable professional development strategy to strengthen science teachers’ pedagogical competence.